Apie Vaižganto „Pragiedrulių" metodą, žanrą, stilių - Radzevičius, Algimantas (Literatūra, 1974)
The article deals with Vaižgantas' "Pragiedruliai" (part 1 - 1918, part 2 - 1920) with respect to the synthetic artistic method that is typical of the writer. The synthetic artistic method is understood here as a synthesis of contradicting and opposite artistic principles and devices, as a phenomenon inherent both in the literary traditions and in the dialectics of the consciousness of the author himself. These premises taken as a basis, the article is an attempt to discuss such questions of the genre, style and methods of Vaižgantas' work that have not been given proper attention as yet.The analysis of the method of the "Pragiedruliai" leads to the conclusion that Vaižgantas was under the influence of two main trends of the Lithuanian literature of the end of the 19th and the beginning of the 20th centuries, namely, the principles of realism (Žemaitė, J. Biliūnas) and the romantic traditions (Maironis). The society and the individual are shown both as they were in reality and as the author would like them to be. Vaižgantas touched upon a number of phenomena that were typical of Lithuania's social life at the end of the 19th and the beginning of the 20th centuries: the oppression of the tsarist regime, the growth of the national liberation movement, the awakening of the national consciousness, important changes in the correlation of classes etc. At the same time the author described those typical social phenomena - the real society of the transitional period in Lithuania - in a romantic way, as a unanimous and active nation. This is a contradictory synthesis of diverse methods.From the point of view of the genre, the "Pragiedruliai" can be ranked somewhere in between a romantic poem and a realistic epopee. Genetically this work is the result of ample experience accumulated in the story genre that was generalized and made use of by the author as he joined several smaller pieces into one literary work by means of a general idea and theme (it is not by chance that the work has the subtitle "Episodes of Struggle for Culture"). The article points out that the structurally dominating principle that unites the seemingly independent episodes of the "Pragiedruliai" is that of epic and lyrical parallels and contrasts. It should also be noted that the image of the author himself is very prominent throughout the work. Otherwise, the "Pragiedruliai" presents no compositional entity, there being no conflict that would develop throughout the episodes.In the style of Vaižgantas' work, one can detect all the styles that existed in Lithuanian prose: epic, lyrical, humorous, satirical, publicistic etc. that constitute a peculiar blend, though the author failed to achieve the synthesis of epical and lyrical elements - that is dramatism. This is partly due to the fact that the writer was too optimistic about the process of national rebirth, being unaware of its deep inner contradictions. No less important is the dominating conception of man based on a harmonious, active and optimistic personality.The article concludes that Vaižgantas' "Pragiedruliai" is one of the most prominent examples of the synthetic artistic method in the classical Lithuanian prose. The birth of this kind of literary work was forewarned by the development of the previous, almost exclusively analytical, Lithuanian prose. In the "Pragiedruliai," however, it was only the general tendency of Vaižgantas' synthetic artistic method that became apparent. The concrete artistic achievements are much more tangible in his later works.